Electrical and Structural Properties of PEMA‐Based Plasticized Polymer Electrolyte. Issue 1 (23rd February 2023) - Singh, Palvinder; Sachdeva, Amit; Bhargava, Cherry; Alheety, Mustafa A; Sharma, Jyoti
Abstract: To resolve the challenges that portable devices confront, polymer electrolytes should be developed. Polymer electrolytes have a number of advantages, including nonflammability, low cost, high stability, no leakage, and a long lifespan. In the present research work, PEMA host polymer with potassium iodide salt enclosure is used with ethylene carbonate (EC) plasticizer to enhance mechanical strength and ionic conductivity. The PEMA+40% wt Kl sample conductivity is measured by complex impedance spectroscopy technique and the maximum conductivity obtained is 3.80×10 −6 S cm ‐1 at room temperature. When EC is added into the solution, there is an increase in conductivity, and the maximum conductivity measured is 4.65×10 −5 S cm ‐1 with sample PEMA+40% wt KI+ %60 wt EC. The prepared electrolyte structural changes and complex formation are subjected to FTIR and XRD characterization techniques. The pore nature of the synthesized polymer electrolyte is investigated using surface electron microscopy.